Evidence map of knowledge translation strategies, outcomes, facilitators and barriers in African health systems - Amanda Edwards; Virginia Zweigenthal; Jill Olivier (BMC, 2019)
Abstract Background The need for research-based knowledge to inform health policy formulation and implementation is a chronic global concern impacting health systems functioning and impeding the provision of quality healthcare for all. This paper provides a systematic overview of the literature on knowledge translation (KT) strategies employed by health system researchers and policy-makers in African countries. Methods Evidence mapping methodology was adapted from the social and health sciences literature and used to generate a schema of KT strategies, outcomes, facilitators and barriers. Four reference databases were searched using defined criteria. Studies were screened and a searchable database containing 62 eligible studies was compiled using Microsoft Access. Frequency and thematic analysis were used to report study characteristics and to establish the final evidence map. Focus was placed on KT in policy formulation processes in order to better manage the diversity of available literature. Results The KT literature in African countries is widely distributed, problematically diverse and growing. Significant disparities exist between reports on KT in different countries, and there are many settings without published evidence of local KT characteristics. Commonly reported KT strategies include policy briefs, capacity-building workshops and policy dialogues. Barriers affecting researchers and policy-makers include insufficient skills and capacity to conduct KT activities, time constraints and a lack of resources. Availability of quality locally relevant research was the most reported facilitator. Limited KT outcomes reflect persisting difficulties in outcome identification and reporting. Conclusion This study has identified substantial geographical gaps in knowledge and evidenced the need to boost local research capacities on KT practices in low- and middle-income countries. Evidence mapping is also shown to be a useful approach that can assist local decision-making to enhance KT in policy and practice.